Women's life writing and early modern Ireland - Eckerle, Julie A., 1971-; McAreavey, Naomi (Women and gender in the early modern world, 2019)
"Women's Life Writing and Early Modern Ireland focuses on women writing in and about seventeenth-century Ireland"--